Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1111/bjh.18401
|View full text |Cite
|
Sign up to set email alerts
|

Quality of end‐of‐life care in multiple myeloma: A 13‐year analysis of a population‐based cohort in Ontario, Canada

Abstract: Summary Optimizing end‐of‐life (EOL) care for multiple myeloma (MM) represents an unmet need. An administrative cohort in Ontario, Canada was analysed between 2006 and 2018. Aggressive care was defined as two or more emergency‐department visits in the last 30 days before death, or at least two new hospitalizations within 30 days of death, or an intensive care unit (ICU) admission within the last 30 days of life. Supportive care was defined as a physician house‐call in the last two weeks before death, or a pall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…We found that a notably higher percentage of patients received active treatment in the last 30, 14 and 7 days before death (68%, 50% and 33%, respectively) compared with previous studies (in which 23% of patients received chemotherapy during the last 14 days). 23 This is important, as monthly drug costs of this limited extension of lifespan (extension) were twice as high as the average monthly overall lifetime drug costs, with the last 3 months constituting 10% of the total lifetime drug costs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that a notably higher percentage of patients received active treatment in the last 30, 14 and 7 days before death (68%, 50% and 33%, respectively) compared with previous studies (in which 23% of patients received chemotherapy during the last 14 days). 23 This is important, as monthly drug costs of this limited extension of lifespan (extension) were twice as high as the average monthly overall lifetime drug costs, with the last 3 months constituting 10% of the total lifetime drug costs.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare utilisation in MM patients during end-of-life has been studied to some extent, showing that a substantial number of patients receive chemotherapy in the last 14 days and are hospitalised in the last 30 days before dying. 23 However, data on which medications are administered and the corresponding drug costs are lacking. 10,11,23,24 In addition, while treatment patterns in daily clinical practice have been reported previously, a complete overview for all patients (i.e., follow-up until death for all patients) is absent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of our population received some type of palliative care in the last year of life ( n = 65,076, 93.0%), and most received a palliative care homecare service in the last 30 days of life ( n = 45,327, 70.0%). The use of supportive care in the last 30 days of life is comparable to other specific cancers, such as 82.1% in multiple myeloma and 69.8% in gynecologic cancers; though these are historically cancers with lower rates of palliative care utilization at end of life [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Encouragingly, despite previous reports of hesitancy by hemato-oncologists (6-8), there seems to be a growing understanding that early integration of PC may be beneficial for HM patients. Recent studies have shown improvements in referral to specialist PC for patients with HM across settings although many HM patients continue to experience aggressive care at the EOL (9,10). We are hopeful that as seen in other fields of medicine, we will see…”
Section: Awarenessmentioning
confidence: 95%